Doubly Stabilized Perovskite Nanocrystal Luminescence Downconverters. Issue 14 (27th April 2022) - Xue, Qi; Lampe, Carola; Naujoks, Tassilo; Frank, Kilian; Gramlich, Moritz; Schoger, Markus; Vanderlinden, Willem; Reisbeck, Patrick; Nickel, Bert; Brütting, Wolfgang; Urban, Alexander S.
Abstract: Halide perovskite nanocrystals (NCs) have emerged as a promising material for applications ranging from light‐emitting diodes (LEDs) to solar cells and photodetectors. Still, several issues impede the realization of the NCs' full potential, most notably their susceptibility to degradation from environmental stress. This work demonstrates highly stable perovskite NCs with quantum yields (QYs) as high as 95% by exploiting a ligand‐assisted copolymer nanoreactor‐based synthesis. The organic ligands thereby serve a dual function by enhancing the uptake of precursors and passivating the NCs. The polymer micelles and ligands thus form a double protection system, shielding the encapsulated NCs from water‐, heat‐ and UV‐light‐induced degradation. The authors demonstrate optoelectronic integrability by incorporating the perovskite NCs as spectrally pure downconverters on top of a deep‐blue‐emitting organic LED. These results establish a way of stabilizing perovskite NCs for optoelectronics while retaining their excellent optical properties. Abstract : This work presents highly luminescent perovskite nanocrystals (NCs) synthesized within a doubly stabilized system comprising block copolymer micelles and organic ligands. The double stabilization protects the NCs against environmentally induced degradation and enhances the luminescence, leading to quantum yields of up to 95%. The NCs are employed as optical downconverters on top of a deep‐blue organic light‐emitting diode, providing bright, spectrally pure electroluminescence.